Impact of interventions to improve recovery of older adults following planned hospital admission on quality-of-life following discharge: linked-evidence synthesis - Debbie Kinsey; Samantha Febrey; Simon Briscoe; Dylan Kneale; Jo Thompson Coon; Daniele Carrieri; Christopher Lovegrove; John McGrath; Anthony Hemsley; GJ Melendez-Torres; Liz Shaw; Michael Nunns (NIHR Journals Library, 2023)
Objectives To understand the impact of multicomponent interventions to improve recovery of older adults following planned hospital treatment, we conducted two systematic reviews, one of quantitative and one of qualitative evidence, and an overarching synthesis. These aimed to: understand the effect of multicomponent interventions which aim to enhance recovery and/or reduce length of stay on patient-reported outcomes and health and social care utilisation understand the experiences of patients, carers and staff involved in the delivery of interventions understand how different aspects of the content and delivery of interventions may influence patient outcomes. Review methods We searched bibliographic databases including MEDLINE ALL, Embase and the Health Management Information Consortium, CENTRAL, and Cumulative Index to Nursing and Allied Health Literature and Allied and Complementary Medicine Database, conducted forward and backward citation searching and examined reference lists of topically similar qualitative reviews. Bibliographic database searches were completed in May/June 2021 and updated in April 2022. We sought primary research from high-income countries regarding hospital inpatients with a mean/median age of minimum 60 years, undergoing planned surgery. Patients experienced any multicomponent hospital-based intervention to reduce length of stay or improve recovery. Quantitative outcomes included length of stay and any patient-reported outcome or experience or service utilisation measure. Qualitative research focused on the experiences of patients, carers/family and staff of interventions received. Quality appraisal was undertaken using the Effective Public Health Practice Project Quality Assessment Tool or an adapted version of the Wallace checklist. We used random-effects meta-analysis to synthesise quantitative data where appropriate, meta-ethnography for qualitative studies and qualitative comparative analysis for the overarching synthesis. Results Quantitative review: Included 125 papers. Forty-nine studies met criteria for further synthesis. Enhanced recovery protocols resulted in improvements to length of stay, without detriment to other outcomes, with minimal improvement in patient-reported outcome measures for patients admitted for lower-limb or colorectal surgery. Qualitative review: Included 43 papers, 35 of which were prioritised for synthesis. We identified six themes: 'Home as preferred environment for recovery', 'Feeling safe', 'Individualisation of structured programme', 'Taking responsibility', 'Essential care at home' and 'Outcomes'. Overarching synthesis: Intervention components which trigger successful interventions represent individualised approaches that allow patients to understand their treatment, ask questions and build supportive relationships and strategies to help patients monitor their progress and challenge themselves through early mobilisation. Discussion Interventions to reduce hospital length of stay for older adults following planned surgery are effective, without detriment to other patient outcomes. Findings highlight the need to reconsider how to evaluate patient recovery from the perspective of the patient. Trials did not routinely evaluate patient mid- to long-term outcomes. Furthermore, when they did evaluate patient outcomes, reporting is often incomplete or conducted using a narrow range of patient-reported outcome measures or limited through asking the wrong people the wrong questions, with lack of longer-term evaluation. Findings from the qualitative and overarching synthesis will inform policy-making regarding commissioning and delivering services to support patients, carers and families before, during and after planned admission to hospital. Study registration This trial is registered as PROSPERO registration number CRD42021230620. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 130576) and is published in full in Health and Social Care Delivery Research; Vol. 11, No. 23. See the NIHR Funding and Awards website for further award information. Plain language summary The problem and why it is important More patients aged 60 or over need planned surgery. These patients are more likely to experience difficulties, such as urinary infections or falls, whilst in hospital, so should not spend more time in hospital than necessary. Hospitals use strategies that shorten hospital stay, but we do not know how older patients, or carers, feel about these, or whether they help patients recover in the long term. Our aims We wanted to know: how leaving hospital sooner affects how older patients feel and recover after planned surgery; how older patients, carers and staff feel about strategies designed to support older patients to go home earlier; which parts of these hospital care strategies work best? What we did We brought together research about hospital care strategies that shorten the length of time older patients spend in hospital. We looked at patient questionnaires and interviews with patients, carers and hospital staff. Patients and carers helped us plan our research, understand our findings and consider who to share these with. Main messages hospital strategies to reduce hospital stay achieve this, without increasing risk of complications; information and follow-up care for patients and carers after discharge are essential; strategies which consider the individual needs of patients and help them understand their treatment, focus on their recovery goals and develop supportive relationships with staff were linked to better outcomes; lots of studies were excluded because they did not use patient questionnaires. Studies using questionnaires often focused on aspects of care delivered whilst patients were in hospital. Carers' voices were often overlooked. What should happen next Research is needed to develop patient questionnaires to more fully capture the experiences of patients and carers and support hospitals to develop care strategies focused on the needs of individual patients and carers. Scientific summary Background The Office for National Statistics predicts that in England the proportion of people aged 65 years and over will increase from 18.2% to 20.7% of the total population between mid-2018 and mid-2028. There has been a steady increase in the number and age of patients admitted for overnight hospital stays for planned or elective procedures, such as hip and knee replacements. Older patients are at increased risk of peri- or post-operative complications such as falls, hospital-acquired infections and cognitive decline, which can impede recovery and require additional support. The COVID-19 pandemic has had a huge impact on waiting lists for elective procedures. Prior to the pandemic, NHS hospitals were under considerable pressure to maintain or improve their provision of care and ensure the cost-effective delivery of services. These pressures have only increased. The British Medical Association suggest the number of people waiting for elective treatment has increased from 4.24 million in March 2020 to 6.84 million in July 2022. Furthermore, NHS monitoring data suggest that between December 2021 and August 2022 the number of patients facing delays in leaving hospital increased by 30%. Many hospital-led, multicomponent organisational strategies have been developed to optimise the time that older people stay in hospital after a planned admission. A recent systematic review of the effectiveness and cost-effectiveness of these interventions showed they were associated with improved clinical outcomes in terms of, for example, length of stay (LOS), readmissions, complications and mortality, or at least performed as well as standard care. However, the subsequent impact on patient outcomes, such as experience, quality of life and participation in meaningful occupations, is largely unknown. Given the ongoing crisis in hospital capacity in the United Kingdom, there is an urgent need to identify, appraise and synthesise the findings from studies considering the influence of multicomponent interventions to enhance recovery on longer-term patient outcomes.